Conversion liquid and process for forming conversion film on surface of non-oriented silicon steel
By using an acid conversion liquid on the surface of silicon steel to form a non-oriented silicon steel surface conversion film, the problem of insufficient generation speed and quality of the silicon steel surface conversion film in the prior art is solved, and the coating performance is significantly improved and the production process is simplified.
Patent Information
- Application Number
- CN202311154579.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-08
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2043-09-08
AI Technical Summary
The prior art is difficult to quickly form high-quality conversion films on the surface of silicon steel, especially on production lines with Qualcomm plate speed, resulting in poor performance such as coating adhesion, scratch resistance and heat resistance.
An acid conversion liquid is used, and the solid content of the liquid is 10 to 30% by weight, and fluoride including titanium, zirconium, hafnium, and silicon is used as the inorganic conversion film component, and additives such as aqueous organic resin and phosphate are added to form a non-oriented silicon steel surface conversion film. This process quickly generates conversion films at room temperature without subsequent rinsing.
It significantly improves the scratch resistance, punching shear processing, salt spray corrosion resistance and heat resistance of silicon steel coatings, improves the performance satisfaction of thicker coating products, and simplifies the production process and improves the controllability and environmental protection of the process.
Smart Images

Figure BDA0004438061790000081 
Figure BDA0004438061790000091 
Figure BDA0004438061790000092
Abstract
Description
Technical Field
[0001] The present invention relates to a coating liquid, a steel plate and a manufacturing method thereof, and in particular to a coating liquid for non-oriented silicon steel, a non-oriented silicon steel plate and a manufacturing method thereof. Background Art
[0002] Electrical steel is widely used as the core material for motors and transformers. In order to reduce the short circuit between electrical steel sheets and increase eddy current loss, an insulating coating needs to be applied on its surface.
[0003] For thick coatings with a dry film thickness of more than 2μm, because the coating contains a considerable amount of inorganic fillers, it is easy for the organic-inorganic mixed amorphous coating formed after the coating is baked and cured to have poor film-forming performance on polar metal substrates with high surface tension.
[0004] In addition, for water-soluble silicon steel insulation thick coating, the coating requires high surface insulation, heat resistance, hot pressing stability and other properties. The coating formula generally contains a lot of submicron-sized inorganic fillers, and its typical content accounts for about 30-70wt% in the coating dry film. Such thick coatings are difficult to produce and prepare on the surface of steel plates, which can easily lead to coating defects and poor film quality, manifested as poor coating adhesion, coating powder falling off to form bright spots, poor coating scratch resistance, coating shedding or paint explosion at the edge during stamping and shearing, etc., which seriously deteriorates the use characteristics of the coating products.
[0005] Therefore, in order to improve the corrosion resistance and adhesion of the metal surface coating, the metal substrate is properly passivated before coating to form an interface conversion film to improve the coating performance, which is a treatment method already adopted in the prior art. For example, the Chinese patent document with the publication number CN104250754A, the publication date of December 31, 2014, and the name "A cold-rolled sheet surface passivation process" discloses such a process. The passivation liquid comprises the following components in percentage by weight: 0.8-1.2% sodium hydroxide, 1.4-1.8% sodium carbonate, 1.5-2.5% sodium tripolyphosphate, 2-4% anhydrous sodium metasilicate, 3-5% phytic acid, 2.5-3.5% sodium bicarbonate, 4-6% sodium benzoate, 5-7% triethanolamine, 3.5-4.5% polyethylene glycol, 0.5-1.5% sodium dodecyl sulfonate, 0.1-0.3% organic silicon defoamer, and the balance is water. The passivation process comprises the following steps: preparing a passivation liquid having the above components, adjusting the pH value to 2.5-3.5, placing the passivation liquid at the position of the oiling process in the cold rolling production line, spraying the passivation liquid onto the surface of the cold rolled steel plate in the form of spraying, and utilizing the residual temperature of the surface of the cold rolled steel plate to react with the surface of the steel plate to form a passivation film.
[0006] The passivation treatment before coating generally includes chromate method, titanium / zirconium method and rare earth conversion method. Among them, titanium / zirconium method is a chromium-free conversion technology that is currently being applied in industry. For example, WO2009 / 115504 discloses the conversion agent components for various application scenarios.
[0007] However, for the chemical treatment of the surface of conventional cold-rolled strip steel, the formation of its passivation film or conversion film requires a considerable reaction time, and the process requires heating to promote the formation of the conversion film. Water treatment may also be required after the film is formed. On the other hand, the continuous annealing and coating production lines of the current mainstream silicon steel production plants generally have a high plate passing speed of 80 to 200 meters per minute. The process equipment and space for the layout of the unit after annealing and before coating are very limited, which determines that the effective generation time of the conversion film on the strip surface is generally a few seconds to more than ten seconds, and there is no condition for rinsing and other water treatment after the conversion film is formed. Therefore, the above-mentioned cold-rolled strip surface chemical treatment method cannot be used for passivation or conversion treatment of silicon steel surfaces after annealing and before coating.
[0008] In addition, the main purpose of the conversion film on the surface of general cold-rolled strip is to enhance rust / corrosion resistance and adhesion, but for the water-soluble environmentally friendly coating on silicon steel, more attention is paid to the coating's scratch resistance, punching and shearing processability, and heat resistance. Summary of the invention
[0009] One of the purposes of the present invention is to provide a conversion liquid for forming a conversion film on the surface of non-oriented silicon steel, which is applied to the silicon steel coil after the last annealing process and before the insulation coating process to form a surface conversion film, and its function is to provide or strengthen the scratch resistance, punching and shearing processability, salt spray corrosion resistance, and heat resistance of the silicon steel coating on the basis of ensuring the main performance of the silicon steel insulation coating, so as to significantly improve the performance satisfaction of the silicon steel thicker coating products. The surface conversion film can be quickly generated at room temperature, and no subsequent water treatment process such as rinsing is required, so the production process is simple and fast.
[0010] In order to achieve the above object, the present invention proposes a conversion solution for forming a conversion film on the surface of non-oriented silicon steel. The conversion solution is acidic and has a solid content of 10 to 30 wt %. The solid content includes:
[0011] The inorganic conversion film component is selected from at least one of the fluorides of titanium, zirconium, hafnium and silicon, and its mass percentage in the conversion liquid is 1 to 10 wt%;
[0012] The water-based organic resin accounts for 0 to 20 wt % of the conversion liquid.
[0013] The present invention controls the amount of conversion film by controlling the solid content and components of the conversion liquid and combining and optimizing subsequent specific conversion processes.
[0014] Within the solid content range defined in the present invention, the higher the solid content of the conversion liquid, the more conversion films that can be formed, the more continuous and denser they are, and the more conducive to improving the subsequent coating-related performance; but at the same time, the more the conversion liquid is consumed, the more difficult it is to control the quality stability of the conversion film, and the narrower the control window of the conversion process.
[0015] In the conversion liquid described in the present invention, the inorganic conversion film component is selected from at least one of the fluorides of titanium, zirconium, hafnium and silicon, for example, one or more substances selected from fluorozirconic acid, fluorotitanic acid, fluorohafnic acid and fluorosilicic acid. It can quickly form a relatively continuous conversion film layer while corroding the surface of silicon steel. The content of the inorganic conversion film component directly determines the generation speed and quality of the conversion film. If the content is higher than the upper limit of the present invention, the uniformity and density of the conversion film will be deteriorated, the use cost will increase, and the high concentration of fluoride treatment will bring difficulties to wastewater treatment.
[0016] Considering that the surface conversion film formed by the present invention is mainly an inorganic component system, and the film forming process is rapid, the conversion film may have local discontinuity, cracks, micropores and other phenomena, the conversion liquid described in the present invention also uses an aqueous organic resin with excellent compatibility and stability as a film-forming material, rather than a water-dispersible emulsion as a film-forming material, to improve the interface adhesion between the inorganic conversion film and the silicon steel coating, to improve the surface quality of the conversion film, and to help the continuity and compactness of the above-mentioned conversion film. However, if its content is higher than the upper limit of the present invention, the stability of the water-soluble aqueous organic resin in the acidic conversion liquid becomes poor, and it will also cover up and weaken the functionality of the inorganic conversion film.
[0017] The pH value of the conversion liquid of the present invention can be 2 to 4. The pH value is a characterization of the composition of the conversion liquid of the present invention. If the pH value is too low, it means that the solid content or concentration of the conversion liquid is high, which is likely to cause large fluctuations in the quality of the conversion film of different production batches, and there are also problems such as large consumption of the conversion liquid and easy corrosion of the tank body. If the pH value is too high, it means that the effective content of the conversion liquid is insufficient, resulting in a decrease in the amount of conversion film generated and the conversion liquid deteriorates quickly.
[0018] Furthermore, in the conversion liquid of the present invention, the inorganic conversion film component at least includes titanium fluoride and / or zirconium fluoride.
[0019] In the present invention, titanium fluoride has the highest reaction activity with the silicon steel substrate interface and the fastest conversion film formation speed, and can be used as a preferred component. In addition, zirconium fluoride can also be preferably used. In addition, titanium fluoride and zirconium fluoride are also preferably used in combination.
[0020] Furthermore, in the conversion solution of the present invention, the solid content thereof is composed of the following:
[0021] The inorganic conversion film component is selected from at least one of the fluorides of titanium, zirconium, hafnium and silicon, and its mass percentage in the conversion liquid is 1 to 10 wt%;
[0022] The water-based organic resin accounts for 0 to 20 wt % of the conversion liquid.
[0023] Furthermore, in the conversion liquid of the present invention, the solid content is 15-20wt%.
[0024] Furthermore, in the conversion liquid of the present invention, the aqueous organic resin is selected from: one of a water-soluble phenolic resin, a polyester resin, and a polyurethane resin.
[0025] Furthermore, in the conversion liquid described in the present invention, the solid content also includes additives, and the additives include phosphates and / or silicon-based additives.
[0026] Furthermore, the mass percentage of the additive in the conversion liquid is 2-15%.
[0027] In a preferred embodiment, the additive can promote the formation speed of the surface conversion film, improve the continuity and density of the surface conversion film, and stabilize the component system of the conversion liquid. However, its content should not be too much. Additives above the upper limit of the present invention may cause the conversion film to be loose or locally enriched, which is not conducive to the heat resistance and punching and shearing performance of the coating.
[0028] Furthermore, in some embodiments, the phosphate is selected from at least one of the phosphates of Mn, Fe, and Co.
[0029] In this embodiment, the phosphates of Mn, Fe and Co have a certain conversion effect on the metal surface.
[0030] Furthermore, in the conversion liquid described in the present invention, the silicon-based auxiliary agent is selected from nano-scale SiO2 sol and / or silane coupling agent.
[0031] As mentioned above, the phosphates of Mn, Fe, and Co themselves have a certain conversion effect on the metal surface. When used in conjunction with a silane coupling agent, the conversion film formed after hybridization with Ti / Zr substances has a higher density and a more continuous film layer.
[0032] In some embodiments, when nano-sized SiO2 sol is used, the film forming speed can be accelerated by utilizing the characteristic of silica sol that it penetrates the substrate quickly.
[0033] The present invention further provides a non-oriented silicon steel, wherein the surface of the non-oriented silicon steel substrate has a surface conversion film formed based on the conversion liquid described above.
[0034] Furthermore, the Ti+Zr content in the surface conversion film is controlled to be 1-800 mg / m 2 .
[0035] Furthermore, in the non-oriented silicon steel of the present invention:
[0036] When 0.2wt%≤(Si+Al)<3.0wt% in non-oriented silicon steel substrate, the Ti+Zr content in the surface conversion film is controlled to be 80~800mg / m 2 ;
[0037] When 3.0wt%≤(Si+Al)≤4.5wt% in the non-oriented silicon steel substrate, the Ti+Zr content in the surface conversion film is controlled to be 1-100mg / m 2 .
[0038] Furthermore, when 0.2wt%≤(Si+Al)<3.0wt% in the non-oriented silicon steel substrate, the Ti+Zr content in the surface conversion film is controlled to be 100-500mg / m 2 .
[0039] Furthermore, when the Si+Al content in the non-oriented silicon steel substrate is 3.0-4.5wt%, the Ti+Zr content in the surface conversion film is controlled to be 3-50mg / m 2 .
[0040] Another object of the present invention is to provide a process for forming a surface conversion film of non-oriented silicon steel, which is carried out after the silicon steel coil has undergone the last annealing process and before the insulation coating process, so as to form a surface conversion film, which is to provide or strengthen the scratch resistance, punching and shearing processability, salt spray corrosion resistance, and heat resistance of the silicon steel coating on the basis of ensuring the main performance of the silicon steel insulation coating, so as to significantly improve the performance satisfaction of the silicon steel thicker coating products. The surface conversion film can be quickly generated at room temperature, and no subsequent water treatment process such as rinsing is required, so the production process is simple and fast.
[0041] In order to achieve the above object, the present invention proposes a process for forming a conversion film on the surface of non-oriented silicon steel, which comprises the following steps: before the insulating coating process:
[0042] The non-oriented silicon steel substrate is subjected to surface immersion treatment using the conversion solution described above; wherein the immersion time is 2 to 15 seconds and the immersion temperature is 5 to 40° C.;
[0043] Dry and solidify to form a surface conversion film.
[0044] The process of the present invention mainly controls the amount of conversion film by controlling and optimizing the solid content and composition of the conversion liquid, as well as the immersion time and temperature. The conversion liquid of the present invention, combined with the process parameters of immersion time and temperature, can ensure the formation of a surface conversion film with controllable quality.
[0045] Furthermore, in the process described in the present invention, the immersion time is 3 to 8 seconds; and / or the immersion temperature is 15 to 30°C.
[0046] Furthermore, in the process described in the present invention, the conversion liquid is placed in a conversion tank, at least one pair of squeeze rollers are arranged at the inlet of the conversion tank, and at least two pairs of squeeze rollers are arranged at the outlet of the conversion tank.
[0047] Two or more pairs of squeeze rollers are set at the outlet of the conversion tank. In addition to preventing the conversion liquid from being carried out of the conversion tank with the strip and causing pollution, it can also control the thickness of the conversion film through pressure adjustment and regulate the spots caused by uneven formation of the conversion film.
[0048] Furthermore, in the process of the present invention, the Ti+Zr content in the surface conversion film is controlled to be 1-800 mg / m 2 .
[0049] Controlling the Ti+Zr content in the surface conversion film within the above range can ensure the quality of the subsequent insulating coating.
[0050] However, the inventors have found through research that the control of the Ti+Zr content in the surface conversion film is related to the composition of the substrate, therefore:
[0051] In some embodiments, when 0.2wt%≤(Si+Al)<3.0wt% in the non-oriented silicon steel substrate, the Ti+Zr content in the surface conversion film is controlled to be 80-800mg / m 2 The Ti+Zr content in the surface conversion film can be further preferably controlled to be 100-500 mg / m 2 .
[0052] In other embodiments, when 3.0wt%≤(Si+Al)≤4.5wt% in the non-oriented silicon steel substrate, the Ti+Zr content in the surface conversion film is controlled to be 1-100mg / m 2 The Ti+Zr content in the surface conversion film can be further preferably controlled to be 3-50 mg / m 2 .
[0053] This is because, the non-oriented silicon steel with the sum of Si+Al content in the substrate of 3.0-4.5wt% is generally a high-grade silicon steel, and there is Al and / or Si oxide enrichment at its interface. Even if the oxide film thickness is relatively low, compared with the low-grade substrate with the sum of Si+Al content of 0.2-3.0wt%, the inorganic non-metallic oxide film modifies the interface micromorphology and significantly reduces the interface surface energy. The contact with the coating is more covalent bonds rather than metal bonds, which is beneficial to improve the relevant properties of the coating, so the amount of conversion film required is relatively small. In actual applications, it is found that for non-oriented high-grade silicon steel, even if the amount of conversion film generated is small, it can improve some of the properties of the final coating. Therefore, this film layer is of transitional nature, and the purpose is to ensure the excellent performance of the final coating above the conversion film.
[0054] However, low-grade silicon steel has little or no interfacial oxide formation, so it must rely on the conversion film to play the role of the interface layer. Therefore, the (Ti+Zr) content in the conversion film must be significantly increased to achieve better final coating performance.
[0055] Furthermore, in the process of the present invention, in the drying and curing step, a hot air drying oven can be used for drying, and the peak temperature of the steel plate metal at the outlet of the hot air drying oven is controlled to be 50-85°C, the dew point of the air in the hot air drying oven is DP<40°C, and the air volume of the drying oven per square meter of the strip steel surface is ≥300m 3 / h.
[0056] Furthermore, in the process of the present invention, surface cleaning is performed before the surface immersion treatment step.
[0057] The purpose of surface cleaning is to remove floating sediment and other contaminants adhering to the surface of the strip in the annealing furnace, and to cool the strip that is about to undergo surface conversion treatment.
[0058] The surface of the strip after annealing is cleaned, specifically by one or more forms of cooling water immersion, spraying, brushing with brush rollers, and electrolytic cleaning. One or more pairs of squeeze rollers can be set at the outlet of the cleaning tank to squeeze out the residual water on the surface of the strip, and a ventilation and drying device can also be set at the outlet of the cleaning tank.
[0059] In some embodiments, the surface temperature of the cleaned steel strip can be controlled to be 10-35°C; the surface cleanliness of the steel strip is no worse than Grade 2 (ISO 8502-3 standard, pressure-sensitive tape method), or the total amount of surface residue is ≤100mg / m 2 (CN102226767A Method for determining residue on the surface of cold-rolled sheet); There should be no water stains on the surface of the steel strip before entering the immersion treatment step that are obviously visible to the naked eye.
[0060] The strip steel meeting the above conditions can enter the subsequent dipping treatment; if the cleanliness level of the silicon steel production unit is high, the strip steel may not need to undergo surface cleaning steps.
[0061] After the silicon steel strip is treated as above, a surface conversion film is formed, and then the surface is subjected to a subsequent insulation coating process to obtain a non-oriented silicon steel product.
[0062] The surface conversion film generated by the present invention; the final silicon steel insulation coating coated thereon can be of C-5 (ASTM A976) or EC-5 (IEC 60404-1-1), or C-6 (ASTM A976) or EC-6 (IEC 60404-1-1) coating.
[0063] The single-sided dry film thickness of the C-5 or C-6 insulating coating coated on the C-4 conversion film can be 0.3 to 7 μm, and the peak temperature range of the baked and cured metal can be 240 to 300°C.
[0064] The conversion liquid and process for forming a conversion film on the surface of non-oriented silicon steel described in the present invention have the following advantages and beneficial effects:
[0065] Although the present invention adds a process after annealing and before coating to form an interface conversion film, it has no effect on the coating coating and baking curing process.
[0066] The conversion liquid of the present invention has controllable impact on the environment and is a water-based, wash-free, short-process, green and environmentally friendly metal surface conversion film treatment liquid.
[0067] By adopting the present invention, a surface conversion film layer can be rapidly generated on the surface of non-oriented silicon steel at room temperature, the process time is generally less than 10 seconds, and there is no need to perform water treatment such as cleaning or rinsing, and the process is simple and convenient.
[0068] The silicon steel insulating coating coated on the surface conversion film generated by the present invention has enhanced anti-rust / corrosion and adhesion properties, as well as improved scratch resistance, punching and shearing processability and heat resistance, thus meeting the stringent requirements for coating performance. DETAILED DESCRIPTION
[0069] The conversion liquid and process for forming a conversion film on the surface of non-oriented silicon steel described in the present invention will be further explained and illustrated below in conjunction with specific embodiments. However, such explanation and illustration do not constitute an improper limitation on the technical solution of the present invention.
[0070] Examples 1-11 and Comparative Examples 1-4
[0071] The surface conversion films of Examples 1-11 were obtained by the following steps:
[0072] (1) Silicon steel materials of grades B50A290 (the sum of Si+Al element contents is 3.8 wt%) and B50A800 (the sum of Si+Al element contents is 1.3 wt%) are selected as substrates.
[0073] (2) After the strip has completed the final annealing process, the strip surface is sprayed with industrial pure water and brushed with a brush roller. A pair of squeeze rollers are set at the outlet of the cleaning tank. The outlet strip temperature is about 25°C, the surface cleanliness is level 1 (ISO 8502-3 standard, pressure-sensitive tape method), and there is no obvious visible water stain on the surface.
[0074] (3) The cleaned strip enters a conversion tank containing conversion liquid for surface immersion treatment. A pair of squeeze rollers are set at the inlet of the conversion tank, and two pairs of squeeze rollers are set at the outlet of the conversion tank. The pressure between the squeeze rollers is 3-4 kg.
[0075] Comparative Examples 1 and 2 adopt steps basically similar to those of the present embodiment, but the solid content of Comparative Example 1 does not satisfy the requirements of the present invention, and the conversion liquid of Comparative Example 2 does not contain inorganic conversion film components.
[0076] Comparative Examples 3 and 4 use a treatment procedure completely different from that of the present invention, in which the substrate is immersed in phosphoric acid for phosphating pretreatment.
[0077] Table 1 lists the solid components and mass percentages of the conversion liquids of various embodiments and comparative examples.
[0078] Table 1.
[0079]
[0080]
[0081] Table 2 lists the specific process parameters of the surface immersion treatment of each embodiment and comparative example.
[0082] Table 2.
[0083]
[0084]
[0085] After the surface impregnation treatment is completed, the conversion liquid in the conversion tank can be recovered and concentrated for waste liquid treatment. The waste liquid can be diluted 20 to 50 times with water, and then calcium hydroxide is added to make the pH value of the dilution ≥ 12. After sufficient mixing and standing, the precipitate is centrally treated and the remaining waste water is discharged. The environmental protection requirements for the discharged wastewater are fluoride ion concentration <20mg / L, phosphorus ion concentration <10mg / L, and chemical oxygen demand COD <500mg / L.
[0086] (4) After the silicon steel strip passes through the conversion tank to form a wet conversion film layer, it enters the hot air drying oven for drying and curing to form a surface conversion film. In a specific example, the air dew point DP in the drying oven can be 20°C, and the drying oven air volume per square meter of the strip steel surface can be 450m 3 / h, the outlet steel plate metal peak temperature PMT is 70 ~ 75 ℃.
[0087] Table 2 also lists the Ti and Zr contents in the surface conversion films formed in various examples and comparative examples. The Ti and Zr contents were measured using an X-ray fluorescence analysis (XRF) method.
[0088] After the surface conversion film is formed, the silicon steel insulation coating coating process can be carried out subsequently, that is, C-6 insulation coating (ASTM A976 standard) is coated on the chemical conversion film, the single-sided dry film thickness can be 4.5±1.2μm, and the peak temperature of the baked and cured metal is 260~280℃ to obtain non-oriented silicon steel products.
[0089] In order to verify the implementation effects of each embodiment and comparative example, samples were taken from embodiments 1-11 and comparative examples 1-4, and the following coating performance tests were performed on them. The test results are listed in Table 3.
[0090] (1) Bending adhesion: According to the GB / T 2522 standard, the four grades of bending adhesion are: "excellent" (grade A), "good" (grade B), "medium" (grade C) and "poor" (grade D).
[0091] (2) Scratch resistance: Use a one-yuan coin with no edge wear. Hold the coin at a 45° angle to the test plate, apply a force of 1 kg, and move the coin parallel to the rolling direction of the steel plate at a speed of 1 cm / s for a distance of 2 cm. Scratch the same area 5 times in parallel. Evaluate the scratch resistance of the coin according to the number of scratches on the visible metal substrate. There are four levels: "excellent" (number of scratches is 0), "good" (number of scratches is 1-2), "fair" (number of scratches is 3) and "poor" (number of scratches is 4-5).
[0092] (3) Punching and shearing processability: Punch or shear the coated steel plate, and observe the coating shedding within 1 mm of the edge under the same conditions to evaluate the punching and shearing processability of the coating. The four levels of punching and shearing processability are: "excellent" (cumulative shedding area within 1 mm of the edge <25%), "good" (25% ≤ cumulative shedding area within 1 mm of the edge <50%), "medium" (50% ≤ cumulative shedding area within 1 mm of the edge <75%) and "poor" (cumulative shedding area within 1 mm of the edge ≥75%).
[0093] (4) Salt spray corrosion resistance: Salt spray corrosion resistance adopts the method of maintaining 7 hours of neutral salt spray NSS. The four levels of corrosion resistance are: "excellent" (corrosion area <10%), "good" (10% ≤ corrosion area <20%), "medium" (20% ≤ corrosion area <40%) and "poor" (corrosion area ≥40%).
[0094] (5) Heat resistance: Heat the coated silicon steel sample to 180℃ for 48h, take it out, cool it, and immerse it in pure water for 24h. Observe the changes such as blistering, wrinkling, and rust on the coating surface to evaluate the compactness of the coating after heat resistance. The four levels of heat resistance are: "excellent" (no change), "good" (total area of change <5%), "medium" (5% ≤ total area of change <10%), and "poor" (total area of change ≥10%).
[0095] Table 3 lists the coating properties of the non-oriented silicon steel sheets of Examples 1-11 and Comparative Examples 1-4.
[0096] Table 3.
[0097]
[0098]
[0099] Note: In Table 3, ◎ means “excellent”; ○ means “good”; △ means “fair”; and × means “poor”.
[0100] It can be seen from Table 3 that the coatings of the non-oriented silicon steel sheets of Examples 1-11 of the present invention have excellent bending adhesion, scratch resistance, punching and shearing processability, heat resistance and corrosion resistance.
[0101] However, since the solid content of the conversion liquid in Comparative Example 1 is lower than the lower limit of the present invention, the coating performance is poor.
[0102] Comparative Example 2 does not contain an inorganic conversion film component, so its coating performance is also poor.
[0103] Comparative Examples 3 and 4 both used phosphating pretreatment by immersing the substrate in phosphoric acid before coating, which is completely different from the technical solution of the present invention. Therefore, the scratch resistance, punching and shearing processability, heat resistance and corrosion resistance of the coating are not good.
[0104] It should be noted that the combination of the various technical features in this case is not limited to the combination described in the claims of this case or the combination described in the specific embodiments. All technical features recorded in this case can be freely combined or combined in any way unless there is a contradiction between them.
[0105] It should also be noted that the above-listed embodiments are only specific embodiments of the present invention. Obviously, the present invention is not limited to the above embodiments, and similar changes or modifications made therewith can be directly derived or easily associated with the contents disclosed by those skilled in the art from the present invention, and all should belong to the protection scope of the present invention.
Claims
1. A conversion solution for forming a conversion film on the surface of non-oriented silicon steel, characterized in that: The conversion liquid is acidic, and has a solid content of 10 to 30 wt %, and the solid content includes: The inorganic conversion film component is selected from at least one of the fluorides of titanium, zirconium, hafnium and silicon, and its mass percentage in the conversion liquid is 1 to 10 wt%; The water-based organic resin accounts for 0 to 20 wt % of the conversion liquid.
2. The conversion solution according to claim 1, characterized in that The solid content is composed of the following: The inorganic conversion film component is selected from at least one of the fluorides of titanium, zirconium, hafnium and silicon, and its mass percentage in the conversion liquid is 1 to 10 wt%; The water-based organic resin accounts for 0 to 20 wt % of the conversion liquid.
3. The conversion solution according to claim 1 or 2, characterized in that: The inorganic conversion film components at least include: titanium fluoride and / or zirconium fluoride.
4. The conversion solution according to claim 1 or 2, characterized in that: The solid content thereof is 15-20wt%.
5. The conversion solution according to claim 1 or 2, characterized in that: The water-based organic resin is selected from: one of water-soluble phenolic resin, polyester resin and polyurethane resin.
6. The conversion solution according to claim 1 or 2, characterized in that: The solid content also includes additives, and the additives include: phosphate and / or silicon-based additives.
7. The conversion solution according to claim 6, characterized in that The phosphate is selected from at least one of the phosphates of Mn, Fe and Co.
8. The conversion solution according to claim 6, characterized in that The silicon-based auxiliary agent is selected from nano-scale SiO2 sol and / or silane coupling agent.
9. The conversion solution according to claim 6, characterized in that The mass percentage of the additive in the conversion liquid is 2-15%.
10. A non-oriented silicon steel, characterized in that: The surface of the substrate of non-oriented silicon steel has a surface conversion film formed based on the conversion liquid according to any one of claims 1 to 9.
11. The non-oriented silicon steel according to claim 10, characterized in that: The Ti+Zr content in the surface conversion film is controlled to be 1-800 mg / m 2 .
12. The non-oriented silicon steel according to claim 11, characterized in that: When 0.2wt%≤(Si+Al)<3.0wt% in non-oriented silicon steel substrate, the Ti+Zr content in the surface conversion film is controlled to be 80~800mg / m 2 ; When 3.0wt%≤(Si+Al)≤4.5wt% in the non-oriented silicon steel substrate, the Ti+Zr content in the surface conversion film is controlled to be 1-100mg / m 2 .
13. The non-oriented silicon steel according to claim 12, characterized in that: When 0.2wt%≤(Si+Al)<3.0wt% in the non-oriented silicon steel substrate, the Ti+Zr content in the surface conversion film is controlled to be 100~500mg / m 2 .
14. The non-oriented silicon steel according to claim 12, characterized in that: When the Si+Al content in the non-oriented silicon steel substrate is 3.0-4.5wt%, the Ti+Zr content in the surface conversion film is controlled to be 3-50mg / m 2 .
15. A process for forming a conversion film on the surface of non-oriented silicon steel, characterized in that: The process includes the following steps: before the insulation coating process: Using the conversion liquid as described in any one of claims 1 to 9 to perform surface immersion treatment on the non-oriented silicon steel substrate; The immersion time is 2 to 15 seconds, and the immersion temperature is 5 to 40°C; Dry and solidify to form a surface conversion film.
16. The process of claim 15, wherein: The immersion time is 3 to 8 seconds; and / or the immersion temperature is 15 to 30°C.
17. The process of claim 15, wherein: The conversion liquid is placed in a conversion tank, at least one pair of squeezing rollers are arranged at the inlet of the conversion tank, and at least two pairs of squeezing rollers are arranged at the outlet of the conversion tank.
18. The process of claim 15, wherein: The Ti+Zr content in the surface conversion film is controlled to be 1-800 mg / m 2 .
19. The process of claim 18, wherein: When 0.2wt%≤(Si+Al)<3.0wt% in non-oriented silicon steel substrate, the Ti+Zr content in the surface conversion film is controlled to be 80~800mg / m 2 ; When 3.0wt%≤(Si+Al)≤4.5wt% in the non-oriented silicon steel substrate, the Ti+Zr content in the surface conversion film is controlled to be 1-100mg / m 2 .
20. The process of claim 19, wherein: When 0.2wt%≤(Si+Al)<3.0wt% in the non-oriented silicon steel substrate, the Ti+Zr content in the surface conversion film is controlled to be 100~500mg / m 2 .
21. The process of claim 19, wherein: When the Si+Al content in the non-oriented silicon steel substrate is 3.0-4.5wt%, the Ti+Zr content in the surface conversion film is controlled to be 3-50mg / m 2 .
22. The process of claim 15, wherein: Surface cleaning is performed prior to the surface immersion treatment step.
Citation Information
Patent Citations
Determination method for residues on the surface of cold rolled sheets
CN102226767A
Cold-rolled plate surface passivation technology
CN104250754A
Optimized passivation on ti- / zr-basis for metal surfaces
WO2009115504A1
Surface-treated metal material and method for producing the same
CN101573472A
Insulation coating and electrical steel material, and preparation method thereof
CN103045058A